Kepuasan Kerja Karyawan Housekeeping Department Pada Sintesa Peninsula Hotel Manado - Iin Andina Prayetni; Sontje M. Sumayku; Roy F. Runtuwene (Universitas Sam Ratulangi, 2018)
Economic development in particular sectors services in Indonesia took place very rapidly services sector. One of the mainstay tourism industry Indonesia, this is the industry that its development was quite rapidly in developing regions or advanced area. Hotel is a large organization has some of the usual part of called department housekeeping department is part of the Organization, as part of the organization department housekeeping has the resources, i.e. employees. the success of the hotel is inseparable from the role of employees. the goal of the research is to the employee's job satisfaction description housekeeping department at Sintesa Peninsula Manado Hotel. This research using methods qualitative nature of the descriptive analysis. Conclusions in finds, each individual have a different level of satisfaction in accordance with the applicable values on him. Then some things that suggested bias is the hotel surveillance in overseeing all aspects of the employee's job satisfaction.Keywords: job satisfaction, housekeeping, sintesa peninsula hotel management